Three-axis MR-conditional robot for high-intensity focused ultrasound for treating prostate diseases transrectally - Yiallouras, Christos; Ioannides, Kleanthis; Dadakova, Tetiana; Pavlina, Matt; Bock, Michael; Damianou, Christakis A. (My University, 2015)
Central.Background: A prototype magnetic resonance image (MRI)-conditional robot was developed for navigating a high-intensity focused ultrasound (HIFU) system in order to treat prostate cancer transrectally. Materials and methods: The developed robotic device utilizes three PC-controlled axes: a linear axis for motion along the rectum, an angular axis for rotation in the rectum, and a linear axis to lift the robot up and down. Experiments with the system were performed in a 1.5-T MRI system using gel phantoms. Result: The robot was successfully operated in a 1.5-T clinical MRI system. The effect of piezoelectric motors and optical encoders was quantified based on the reduction of signal to noise ratio. Discrete and overlapping lesions were created accurately by moving the HIFU transducer with the robotic device. Conclusion: An MRI-conditional HIFU robot was developed which can create controlled thermal lesions under MRI guidance. The intention is to use this robot transrectally in the future for the treatment of prostate cancer.
Keywords: Robotics; Gel phantom; High intensity focused ultrasound; high intensity focused ultrasound device